The taste of compassion: Influencing meat attitudes with interhuman and interspecies moral appeals. (1st January 2022) - Pohlmann, Attila
Abstract: Consumers of meat products are generally shielded from the moral dissonance associated with the killing of livestock. Nonetheless, consumers increasingly look for ways to reduce or avoid meat in their diets due to concerns about individual health and the harmful global impacts of meat production. Campaigns that promote plant-based diets seek to facilitate such efforts by appealing to consumers' compassion, but the effects of such moral appeals on immediate food choice have not been studied. The literature on the psychology of meat consumption, its gendered associations in western cultural contexts are reviewed, and a compassion appraisal model for ethical food choice is tested. In a longitudinal restaurant field study and three laboratory experiments, the effects of interhuman as well as interspecies compassion appeals on meat-containing vs. meatless food choices are investigated. Compassion mediates ethical food choices, but is moderated by denial of the harmful consequences of meat production. Threats to masculinity that are often associated with meat advertising increase men's likelihood to choose meat instead of a vegetarian option. Overall, results indicate that men are less amenable to reduce their meat consumption and that they evaluate vegetarian options as less palatable when exposed to compassion appeals. These effects were opposite for women. Implications for meatless food products and for consumer well-being are discussed.